2016
DOI: 10.3389/fmicb.2016.00071
|View full text |Cite
|
Sign up to set email alerts
|

Carbon and Nitrogen Uptake of Calcareous Benthic Foraminifera along a Depth-Related Oxygen Gradient in the OMZ of the Arabian Sea

Abstract: Foraminifera are an important faunal element of the benthos in oxygen-depleted settings such as Oxygen Minimum Zones (OMZs) where they can play a relevant role in the processing of phytodetritus. We investigated the uptake of phytodetritus (labeled with 13C and 15N) by calcareous foraminifera in the 0–1 cm sediment horizon under different oxygen concentrations within the OMZ in the eastern Arabian Sea. The in situ tracer experiments were carried out along a depth transect on the Indian margin over a period of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 54 publications
(101 reference statements)
3
12
0
1
Order By: Relevance
“…To maintain an optimum energy budget, expenses of metabolic maintenance could therefore be compensated by a shift of H. germanica populations towards the subtidal zone. Foraminiferal C : N ratios are known from bathyal foraminifera of the Sagami Bay and from oxygen minimum zones of the Arabian Sea, where they range from 2.6 to 6.4 (Nomaki et al, 2008Enge et al, 2016). In our study, both species showed similar C : N ratios and natural 13 C and 15 N signatures (Tables 1 and 4), indicating equivalent trophic levels and similar nutritional demands.…”
Section: Relationships Between Carbon and Nitrogen Uptake And Cytoplasupporting
confidence: 67%
See 3 more Smart Citations
“…To maintain an optimum energy budget, expenses of metabolic maintenance could therefore be compensated by a shift of H. germanica populations towards the subtidal zone. Foraminiferal C : N ratios are known from bathyal foraminifera of the Sagami Bay and from oxygen minimum zones of the Arabian Sea, where they range from 2.6 to 6.4 (Nomaki et al, 2008Enge et al, 2016). In our study, both species showed similar C : N ratios and natural 13 C and 15 N signatures (Tables 1 and 4), indicating equivalent trophic levels and similar nutritional demands.…”
Section: Relationships Between Carbon and Nitrogen Uptake And Cytoplasupporting
confidence: 67%
“…Simultaneous detection of both stable isotopes allows us to determine the ratio in which pC relative to pN is retained in bulk foraminiferal cytoplasm over time. This helps to interpret phytodetrital uptake in relation to foraminiferal carbon and nitrogen coupling (Enge et al, 2016;Evrard et al, 2010;Hunter et al, 2012) and temperature influences might show imbalances of these ratios between treatments. Benthic foraminifera are used in the assessment of (palaeo-) environmental data.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The laboratory feeding experiment was performed in incubation chambers, adjusted to 20 • C, 25 • C and 30 • C. To obtain direct estimates of the uptake of carbon and nitrogen, phytodetritus was labelled with stable isotopes ( 13 C, 15 N). This method has provided important data on the in situ feeding behaviour of foraminifera in various environments (Moodley et al, 2002;Enge et al, 2016;Moodley et al, 2000;Middelburg et al, 2000;Witte et al, 2003;Nomaki et al, 2005Nomaki et al, , 2009Nomaki et al, , 2011Sweetman et al, 2009;Enge et al, 2011;Jeffreys et al, 2013). The temperatures chosen for this experiment correspond to experimentally determined values that cover optimum or tolerance ranges for growth and reproduction in laboratory cultures of intertidal foraminifera (Bradshaw, 1957(Bradshaw, , 1961Lee and Muller, 1973).…”
mentioning
confidence: 99%